HIV as an independent risk factor for incident lung cancer. - Sigel, Keith; Wisnivesky, Juan; Gordon, Kirsha; Dubrow, Robert; Justice, Amy; Brown, Sheldon T; Goulet, Joseph; Butt, Adeel A; Crystal, Stephen; Rimland, David; Rodriguez-Barradas, Maria; Gibert, Cynthia; et al. (AIDS (London, England), 2012)
It is unclear whether the elevated rate of lung cancer among HIV-infected persons is due to biological effects of HIV, surveillance bias, or excess smoking. We compared the incidence of lung cancer between HIV-infected and demographically similar HIV-uninfected patients, accounting for smoking and stage of lung cancer at diagnosis.
Keywords: Adult; Age Factors; Aged; Aged, 80 and over; Female; HIV Infections; Humans; Incidence; Lung Neoplasms; Male; Middle Aged; Risk Factors; Smoking; United States; Veterans; Young Adult